Occupation and fertility on the frontier: Evidence from the State of Utah - Thomas N. Maloney; Heidi Hanson; Ken R. Smith (The University of Utah, Department of Economics, 2013)
The United States in the 19th century was marked by initially quite high fertility levels but also by the onset of a relatively early and steep decline in fertility. Most of what we know about these patterns in the US comes from aggregate (typically county or state level) data. We provide new, micro-level evidence on patterns of fertility change in the US in the late 19th and early 20th centuries. We use records from the Utah Population Database (Mineau 2007), particularly family history records linked to death certificates, and focus on occupational differentials in the level of, and change in, the number of children born to a woman, along with several other fertility-related behaviors. Our preliminary results suggest that there was substantial commonality in the timing of change in fertility across socioeconomic strata (as measured by spouse's occupation). Still, some differences in these behaviors across occupational classes did emerge during the era of the fertility transition. The households of white collar workers and of farmers typically defined the bounds of these behaviors, with white collar households often leading change and other occupational groups, including farm households, closing the gap over time.
Keywords: J13; N31; 330; fertility; fertility transition; socioeconomic status; United States; history